NILPOTENCY OF DERIVATIONS - Kadem, Sameer; Majeed , Abdulrahman H. (Iraqi Journal of Science, 2022)
In this paper we show the nilpotency of nilpotent derivation of simeprime Γ-ring with characteristic 2 must be a power of 2 and we show the nilpotency of a nilpotent derivation of simeprime Γ-ring is either odd or a power of 2 without torsion condition.